Pola Pemahaman Hadits di Kalangan Ulama’ Fiqih Madzhab Syafi’i - Muhammad Najib (Cendekia, 2022)
This article is a simple effort to reveal the understanding of Shafi'i scholars on hadith, starting from the study of the framework placed by Imam Shafi'i in his madhab, specifically in the study of hadith. This is important considering that apart from the fact that the Shafi'i madhab is the madhab with the largest followers, it also cannot be separated from the figure of Imam Shafi'i as the founder of the madhab which is said to be nicknamed nashir al-sunnah. The method used in uncovering the above is through tracing and studying various literature with documentation techniques, using descriptive and comparative data analysis. The result is that the study of hadith among Shafi'I scholars cannot be separated from the framework laid down by Imam Shafi'I who is very accommodating to hadith, and open. This is reflected in his acceptance of the hadith of Sunday or khabar al-wahid in the term Shafi'i, as well as the problem-solving that he offers when there is a contradiction between the hadiths, where al jam'u, naskh, and tarjih before finally being perfected with tawaqquf become a concrete solution to sit the hadith as a source of law that must be accepted and should not be wasted.